An AHP-based approach to credit risk evaluation of mortgage loans - Ferreira, F. (2015)
Mortgage loans for home purchase require careful analysis by all parties involved in the transaction, and credit-scoring is usually adopted to assist the decision process. From a credit institution standpoint, credit-scoring for mortgage loan risk evaluation becomes even more important in scenarios of economic turbulence and recession, primarily because of the severe restrictions imposed on credit availability that result from reduced access to both money and debt markets and subsequent decreasing liquidity. Employing an AHP – Analytic Hierarchy Process – based approach in the creditscoring system used by one of the major banks in Portugal, this study proposes a methodological framework conceived to adjust trade-offs among evaluation criteria and provide decision makers with a more transparent mortgage risk evaluation system. Practical implications of our framework are also discussed.